Analisis Nilai pH dan Sensori Yoghurt dan Soyghurt dengan Proses Fermentasi yang Berbeda - Syafitri, Yosi; Nasution, Syahrizal; Fithriyani, Dina (Communication in Food Science and Technology, 2022)
Yoghurt is a milk product that lactic acid bacteria have fermented. Soyghurt drinks have gained popularity in recent years. Soyghurt is a fermented soymilk drink that tastes similar to yoghurt. Commercial starter cultures or back-sloping methods can make yoghurt and soyghurt. The purpose of this study was to compare the pH and sensory characteristics of yoghurt and soyghurt made using different production methods. Back-slope yoghurt, commercial yoghurt starter, back-slope soyghurt, and commercial starter soyghurt were the four treatments used in this study. The fermentation process was carried out at room temperature (27-30 °C) for 24 hours. Color, aroma, taste, and texture were all measured, as well as the pH value. The sample shows the product has a pH value between 4 and 5. The low pH value in yoghurt and soyghurt is due to the growth of lactic acid bacteria. Based on sensory analysis, commercial starter culture produced the best yoghurt and soyghurt rather than the back-slope method in sensory attributes of taste, aroma, and texture. In addition, the color of soyghurt products appeared to be darker than yoghurt products.